Bourdieu’s Habitus and Field: Implications on the Practice Aisyiyah Cadre Candidacy of Legislative Elections 2024 - Fitriyah, Ikhrotul; Wahyuni, Lilik; Utaminingsih, Alifiulahtin (Universitas Muhammadiyah Malang, 2025)
This article discuss Pierre Bourdieu's concepts of habitus and field about the candidacy practices of Aisyiyah cadres running for legislative positions in East Java in the 2024 elections. Concerning the discourse of habitus formed from the socio-religious habitus formed through the experience in the Aisyiyah organization, it transformed when they entered a political structure that was patriarchal, competitive, and transactional, and not gender-neutral. The method used in this study is qualitative with a phenomenological approach, the data source used is primary data, collected through semi-structured interviews with related sources. The results of this study show that the disposition of Aisyiyah cadres in the political parties PAN, UMMAT and PDIP is based on inherent values in themselves and life journeys. In running their candidacy, they must adapt and build a strategy to navigate the contest arena by maximizing their modalities. The way is to approach party elites, local political figures, and organizational networks, take advantage of party assistance for campaigns, pengajian, and socialization with the transfer of their expertise.